A comparison of continuous and split exercise sessions on excess post-exercise oxygen consumption and resting metabolic rate - Almuzaini, K. S.; Potteiger, J. A.; Green, S. B. (Medicine & Science in Sports & Exercise, 1997)
The effect of splitting a 30-min exercise bout into two equal 15-min sessions on excess post-oxygen consumption (EPOC) and resting metabolic rate was determined. Ss (Males = 10) cycled for 30 minutes at 70% VO2max followed by a 40-min measurement of EPOC. The two 15-min trials were performed with six hours of rest between. Each split-session trial was followed by 20 minutes of EPOC measurement. The combined magnitude of the EPOCs from the split sessions was significantly greater than from the single session. However, there was no difference in resting metabolic rates between the two protocols. Implication: Splitting training tasks into intervals or repetitions will increase the amount of oxygen consumed and needed to be repaid after each unit when compared to performing the same distance at the same workload in a continuous manner. Intermittent training tasks place a greater load on the oxygen transport system than do continuous tasks.